Frequency scanning Fabry–Pérot cavity antenna with single 2D‐varying partial reflecting surface. Issue 11 (2nd July 2020) - Zhan, Junlin; Xu, Feng; Liu, Shui; Deng, Senshen; Yang, Ling; Qiang, Jingxia
Abstract : This study presents a frequency scanning Fabry–Pérot cavity antenna with a single 2D varying partially reflecting surface (PRS) operating from 9.4 to 10.6 GHz. A probe‐fed stacked rectangular patch antenna is applied as the primary source. A PRS consisting of 9 × 9 cells, whose sizes vary with azimuth, is mounted upon the source to modulate the phase efficiently. Due to the opposite correlations between scan angle and frequency in the forward and backward regions, phase distributions in the forward region are dominant in frequency scanning. The scan angle increases with frequency, as the negative correlation between the reflection phase of PRS and frequency. It is demonstrated that the beam angle is scanned from 11° to 35° with over 10 dBi gain and over 88% radiation efficiency within the band. The results in simulations and measurements validate the frequency scanning performance. It also provides the possibility that phase distributions in the forward region and the backward region could have the same weights in frequency scanning for better performances. Besides, without electronic/mechanical tuning, or PRS size varying, the proposed antenna is simple for design and operation.